Impact of Exogenous Lactiplantibacillus plantarum on the Gut Microbiome of Hematopoietic Stem Cell Transplantation Patients Colonized by Multidrug-Resistant Bacteria: An Observational Study - Bruna D. G. C. Moraes; Roberta C. R. Martins; Joyce Vanessa da Silva Fonseca; Lucas A. M. Franco; Gaspar C. O. Pereira; Thais F. Bartelli; Marina F. Cortes; Nazareno Scaccia; Carolina F. Santos; Priscila T. Musqueira; Leonardo J. Otuyama; Victor S. Pylro; et al. (Antibiotics)
Background: Lactiplantibacillus plantarum can inhibit the growth of multidrug-resistant organisms (MDROs) and modulate the gut microbiome. However, data on hematopoietic stem cell transplantation (HSCT) are scarce. Aim: In an observational study, we assessed the impact of L. plantarum on the modulation of the gut microbiome in HSCT patients colonized by MDROs. Methods: Participants were allocated to an intervention group (IG = 22) who received capsules of L. plantarum (5 × 109 CFU) twice per day until the onset of neutropenia or a control group (CG = 20). The V4 region of the 16S bacterial rRNA gene was sequenced in 87 stool samples from a subset of 33 patients (IG = 20 and CG = 13). The Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt2) program was used to predict metagenome functions. Results: L. plantarum demonstrated an average 86% (±11%) drug-target engagement at 43 (±29) days of consumption and was deemed safe, well-tolerated, and associated with an increase in the abundance of the Lactobacillales (p < 0.05). A significant increase in Lactococcus and a reduction in Turicibacter (p < 0.05) were identified on the second week of L. plantarum use. Although Enterococcus abundance had a greater rise in the CG (p = 0.07), there were no significant differences concerning the Gram-negative MDROs. No serious adverse effects were reported in the IG. We observed a greater, non-significant pyruvate fermentation to propanoate I (p = 0.193) relative abundance in the IG compared with the CG. L. plantarum use was safe and tolerable by HSCT patients. Conclusions: While L. plantarum is safe and may impact Enterococcus and Turicibacter abundance, it showed no impact on Gram-negative MDRO abundance in HSCT patients.